Economic Adaptability in the Absence of Democratic Corporatism: Explaining Lithuania’s Export Performance* - Kuokštis, Vytautas; Vilpišauskas, Ramūnas (Politologija, 2022)
Viewed in light of democratic corporatism literature, Lithuania is a deviant case. Although it lacks essential institutional prerequisites deemed important for export success and flexible adaptation to external shocks, the small Baltic country has been among the best performers in the European Union on these dimensions. Lithuania has become very internationally integrated and has managed to quickly adjust to numerous shocks, such as the Russian financial crisis of 1998–99, the Global Financial Crisis of 2008–2009, and the COVID-19 pandemic. In this article, we analyse Lithuania’s export specialization and show how particular institutional elements have supported flexible adaptation and competitiveness improvements: we cover the labour market, state’s involvement in terms of domestic compensation and public goods provision, education and skills, and the role of political legitimacy. Lithuania’s case has implications for the literature on the political economy of small states and the debate regarding the middle-income trap.